Resistance to activated protein C, the FV: Q506 allele, and venous thrombosis - Dahlbäck, B.; Hillarp, A.; Rosen, S.; Zöller, B. (Hämostaseologie, 1998)
Vitamin K-dependent protein C is an important regulator of blood coagulation. After its activation on the endothelial cell surface by thrombin bound to thrombomodulin, it cleaves and inactivates procoagulant cofactors Va and Villa, protein S and intact factor V working as cofactors. Until recently, genetic defects of protein C or protein S were, together with antithrombin III deficiency, the established major causes of familial venous thromboembolism, but they were found in fewer than 5-10% of patients with thrombosis. In 1993, inherited resistance to activated protein C (APC) was described as a major risk factor for venous thrombosis. It is found in up to 60% of patients with venous thrombosis. In more than 90% of cases, the molecular background for the APC resistance is a single point mutation in the factor V gene, which predicts substitution of an arginine (R) at position 506 by a glutamine (Q). Mutated factor V (FV: Q506) is activated by thrombin or factor Xa in normal way, but impaired inactivation of mutated factor Va by APC results in life-long hypercoagulability. The prevalence of the FV:Q506 allele in the general population of Western countries varies between 2 and 15%, whereas it is not found in several other populations with different ethnic backgrounds. Owing to the high prevalence of FV:Q506 in Western populations, it occasionally occurs in patients with deficiency of protein S, protein C, or antithrombin III. Individuals with combined defects suffer more severely from thrombosis, and often at a younger age, than those with single defects, suggesting severe thrombophilia to be a multigenetic disease.
Keywords: APC-resistance; factor V; protein C; protein S; thrombosis